Enriching Structural Diversity of Alkynyl‐Protected Gold Nanoclusters with Chlorides - Li, Jiao‐Jiao; Guan, Zong‐Jie; Yuan, Shang‐Fu; Hu, Feng; Wang, Quan‐Ming (Angewandte Chemie International Edition, 2021)
The synthesis and isolation of alkynyl/chloride‐protected gold nanoclusters is described. Silica gel column chromatography is effective in isolating gold nanoclusters from the as‐synthesized cluster mixture to give the clusters Na[Au25L18] (Au25), [HNEt3]3[Au67L32Cl4] (Au67), [HNEt3]4[Au106L40Cl12] (Au106), L=3,5‐bis(trifluoromethyl)‐phenylacetylide. Au67 and Au106 are new clusters; the structures were determined by X‐ray single‐crystal diffraction. Au67 contains a distorted Au18 Marks decahedron shelled by an irregular Au32 and further protected with two V‐shaped Au2L3, 13 linear AuL2 staples and 4 chlorides. Au67 is the first structurally determined 34e superatomic gold nanocluster. Au106 is composed of 106 Au atoms co‐protected by alkynyls and chlorides. It has a Au79 kernel, like in Au102(p‐MBA)44. The surface structure of Au106 includes 20 linear Au‐alkynyl staples, 5 Cl‐Au‐Cl and 2 Cl‐Au motifs. These three gold nanoclusters show size‐dependent electrochemical properties. The combination of chloride and alkynyl as protecting agents leads to the formation of large gold nanoclusters. Silica gel column chromatography results in the successful isolation and crystallization of atomically precise gold nanoclusters [HNEt3]3[Au67L32Cl4] (Au67), [HNEt3]4[Au106L40Cl12] (Au106), where L=3,5‐bis(trifluoromethyl)‐phenylacetylide. They are all superatomic clusters, and show size‐dependent electrochemical properties.